Effect of Brine Time on Quality of Wet-Salted Fish - Zuliyan Agus Nur Muchlis Majid; Novianti Adi Rohmanna; Syifa’ Robbani (TROPICAL WETLAND JOURNAL, 2020)
Stingrays or Dasyatis sp. was one kind of fishery commodities. This product was perishable, so it required careful handling through the handling process. Fish preservation was an alternative that can be applied. This study aimed to protect the fresh fish quality throughout the handling process before it was processed further. This research method used the wet-salting method. The principle of this method was to keep the product for a long time in brine for 0h (control/fresh fish), 1h, 2h, and 3h. The analysis achieve was TVB-N, TMA, TPC, total crude protein, and pH. The effect of time in brine on the result showed significant variation with p-value < 0.05. pH value was significantly correlated with TVB-N and total protein, while, TPC was significantly correlated with total crude protein. These conclusions, the fish product for 1h in brine was the best treatment.